Systematic Review and Meta-Analysis of Risk Factors Associated with Postoperative Stress Hyperglycemia in Patients without Diabetes Following Cardiac Surgery - Mengli Zhang; Ziyi Zhang; Ningning Zhu; Lulu Wang; Hui Huang; Yike Wang; Fang Xue (Reviews in Cardiovascular Medicine)
Background: To systematically evaluate risk factors for stress-induced hyperglycemia in patients without diabetes after cardiac surgery. Methods: Databases including CNKI, WanFang data, VIP, SinoMed, PubMed, Web of Science, Embase, and the Cochrane Library were searched using computer retrieval. The data were subjected to an in-depth meta-analysis using RevMan 5.4 and Stata 15.0 software. Results: This study involved 11,645 postoperative cardiac surgery patients, including 8 case-control studies and 3 cohort studies, over which 18 risk factors were identified. The results of the meta-analysis indicated that statistically significant risk factors included age >65 years [odds ratios (OR) (95% CI ) = 3.47 (2.61–4.32)], female gender [OR (95%) = 1.54 (1.34–1.76)], combined heart valve and coronary artery bypass surgery [OR (95%) = 1.82 (1.23–2.70)], ejection fraction <40% [OR (95%) = 1.38 (1.17–1.63)], history of heart surgery [OR (95%) = 1.30 (1.06–1.59)], myocardial infarction [OR (95%) = 1.17 (1.05–1.31)], hyperlipidemia [OR (95%) = 0.76 (0.67–0.86)], hypertension [OR (95%) = 1.12 (1.03–1.22)], anticoagulant medication [OR (95%) = 0.77 (0.65–0.90)], cardiopulmonary bypass time >2 hours [OR (95%) = 20.26 (17.03–23.48)] and history of cardiopulmonary bypass [OR (95%) = 1.24 (1.09–1.41)]. Conclusions: Current evidence suggests that there are key risk factors for postoperative stress hyperglycemia in patients without diabetes who have undergone cardiac surgery. These factors can help identify patients at a high risk of perioperative stress hyperglycemia during cardiac surgery. This evidence provides a basis for healthcare professionals to develop predictive management strategies for perioperative stress hyperglycemia in patients without diabetes. However, more high-quality studies are required to address the limitations of the current research. The PROSPERO registration: CRD42024479215, https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=479215.